Peran Tinggi dan Berat Badan terhadap Kemampuan Lompatan Vertikal dan Fleksibilitas pada Atlet Bola Voli Putri Profesional - Jesy Aisyah; Taufik Rahman; Noer Wachid Riqzal Firdauz (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This research explores the connection between height and weight concerning vertical jump capabilities (power leg) and flexibility in proffesional female volleyball players. A cross-sectional design was employed, utilizing a quantitative correlation method. The sample comprised 14 athletes chosen through purposive sampling based on their active training status and absence of injuries. Height and weight were assessed using a stadiometer and digital scales, while vertical jump and flexibility ability were evaluated with testing equipment according to Permenpora No. 15 of 2024 standards. The data analysis was conducted using the Spearman correlation test with a significance threshold of p<0.05. The findings indicated no significant relationship between height or weight with vertical jump (p=0.223 and p=0.187) or flexibility (p=0.171 and p=0.258). The mean values for vertical jump (45.0 cm) and flexibility (19.79 cm) fell short of the national standard. In summary, neither height nor weight significantly impacted these physical attributes. A training regimen concentrating on enhancing muscle strength and flexibility is essential to promote optimal performance in athletes.